Microbial inoculation to improve plant performance in mine‐waste substrates: A test using pigeon pea (Cajanus cajan). (4th January 2022) - Wong, Wei San; Morald, Tim K.; Whiteley, Andrew S.; Nevill, Paul G.; Trengove, Robert D.; Yong, Jean W. H.; Dixon, Kingsley W.; Valliere, Justin M.; Stevens, Jason C.; Veneklaas, Erik J.
Abstract: Mining activities alter soil physicochemical and biological properties that are critical for plant establishment. Revitalisation of soil biological properties via microbial inoculations can potentially be adopted to improve vegetation restoration. Here, we evaluate the feasibility of using beneficial microorganisms in the form of commercially available inoculants to enhance plant performance in a non‐toxic and infertile mine‐waste substrate, using pigeon pea [ Cajanus cajan (L) Millsp.] as a test plant. Six treatments were established to investigate the effects of inoculants ( Bradyrhizobium spp., microbial mix and uninoculated controls) and water availability (low and moderate) in a factorial design over 6 months. Plant performance was determined by physiological parameters (leaf gas exchange, leaf carbon, nitrogen and stable isotopes) and growth (height and biomass). Plant xylem sap phytohormones were measured to determine the plants' physiological status and effects of inoculation treatments. Results revealed that water had a greater effect on plant growth than inoculation treatments. Inoculation treatments, however, improved some physiological parameters. This study suggests that physical conditions such as soil moisture and nutrient availability may occlude more subtle (direct or interactive) effects of beneficial soil microbes on plant growth and plant condition. Prior knowledge on the biological and physicochemical properties of the soil to be amended, and on plant species‐specific responses, would be needed to customise microbial inoculants for maximum benefits to ecological restoration, to support future adoption of this practice.